Can progression of odontogenic infections to cervical necrotizing soft tissue infections be predicted?. Issue 2 (February 2017) - Zemplenyi, K.; Lopez, B.; Sardesai, M.; Dillon, J.K.
Abstract: The progression of odontogenic infections to necrotizing soft tissue infections (NSTIs) is unknown. The Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score is used to predict risk of NSTI. This study aimed to (1) estimate the frequency at which odontogenic infections progress to NSTIs, (2) measure the value of LRINEC in predicting progression to NSTI, and (3) estimate the charges associated with managing NSTIs. This retrospective cohort study enrolled all subjects admitted for the management of odontogenic infections from 2001 to 2013. The primary predictor was the LRINEC score. The primary outcome was NSTI. The secondary outcome was billing charges. Descriptive and bivariate statistical analyses were performed, with significance set at a P -value of <0.05. Of 479 odontogenic infections, (1.0%) progressed to NSTI. The mean LRINEC for NSTI was 5.8 and for odontogenic infection was 3.4 ( P = 0.043). LRINEC parameters for the prediction of NSTIs had 60% sensitivity, 68.4% specificity, 20% positive predictive value, and 92.9% negative predictive value. The mean charge for NSTI was 319, 337 and for odontogenic infections was 19, 291 ( P = 0.051). One percent of odontogenic infections progressed to NSTIs. The LRINEC score was not able to identify all NSTIs. NSTIs are 16 times more costly.